PEDAGOGICAL BASIS FOR INCREASING THE EFFECTIVENESS OF THE FORMATION OF PEDAGOGICAL RESPONSIBILITY AMONG FUTURE DEFECTOLOGISTS - Nodira Mirbabaeva (American Journal Of Social Sciences And Humanity Research, 2024)
The main idea of the article is that improving the conditions for the formation of professional motivation in future speech therapists is an urgent problem. The scientifically grounded views of foreign and domestic scientists on the formation of professional motivation are presented. The system of formation of professional motivation of future defectologists studying at the university was also discussed.